Exploring the Challenges of the Beneficiaries of the Sustainable Livelihood Program (SLP) of the Department of Social Welfare and Development: Enhance Development Plan - Chavez, Jessie Mar A. (Indonesian Journal of Advanced Research, 2025)
This study explores the challenges and adaptive strategies of beneficiaries of the Sustainable Livelihood Program (SLP) engaged in both traditional marketing and online selling. Traditional entrepreneurs contend with limited market access, seasonal disruptions, regulatory barriers, and financial instability, while online sellers face intense competition, low customer trust, and inadequate digital literacy despite broader reach. Both groups demonstrate resilience: traditional sellers leverage community trust and personalized service while gradually integrating digital tools, whereas online sellers adopt customization and resource-conscious practices to remain competitive. The study accentuates the need for a comprehensive support framework through financial access, inter-agency collaboration, and capacity building in digital marketing and business management. Targeted, needs-based interventions are critical for fostering inclusive growth and ensuring long-term sustainability among SLP beneficiaries.